PEMBERIAN HIDRASI CAIRAN DAN SNACK ASIN PREDONASI SEBAGAI PENCEGAHAN REAKSI VASOVAGAL PADA PENDONOR DARAH PERTAMA : CASE SERIES : PREDONATION FLUID HYDRATION AND SALTY SNACKS AS PREVENTION OF VASOVAGAL REACTIONS IN FIRST-TIME DONORS: CASE SERIES - Ma'ripah, Isnan; Pratiwi, Sri Hartati; Nugraha, Bambang Aditya (STIKes Mitra Keluarga, 2025)
Introduction : Vasovagal reactions after blood donation cause dizziness, nausea, and even loss of consciousness, thus disrupting the donor's comfort and the donation process. Vasovagal reactions can reduce the donor's interest in donating blood again. In fact, blood donation not only provides benefits for people in need, but also provides benefits for the donor, namely stimulating the production of new blood cells, reducing the risk of coronary heart disease, and routine health checks every time they donate blood. To overcome this problem, interventions are needed to prevent vasovagal reactions. One of these interventions is fluid hydration and consumption of salty snacks 30 minutes before donation. This study aims to determine the effects of fluid hydration and consumption of salty snacks in preventing vasovagal reactions in first-time donors. Method: The design of this study was a case series on 5 cases of first donors with nursing problems of hypovolemia risk. Result: The results of this study indicate that providing fluid hydration and consuming salty snacks before donating blood can reduce the incidence of vasovagal reactions in cases. Conclusion: Providing fluid hydration and consuming salty snacks before donating blood is one option in developing a strategy for managing the risk of vasovagal reactions.